Direct sensor orientation for large scale mapping - Potential, problems, solutions - Yastikli, N; Jacobsen, K (WILEY, 2005)
Georeferencing is one of the most important tasks in photogrammetry. Traditionally it has been achieved indirectly using the well-known method of aerial triangulation. With the availability of integrated GPS and inertial measurement units (IMU), this situation changed. Direct determination of exterior orientation is now possible. Today, direct and integrated sensor orientation is usedfor a wide range of sensors including lidar and SAR, as well as for digital line scanner systems and aerial cameras. This paper investigates the performance of direct and integrated sensor orientation for large scale mapping using the data-set of the Integrated Sensor Orientation test of the European Organisation for Experimental Photogrammetric Research (OEEPE-now known as EuroSDR). The concept, potential, problems and solutions of direct and integrated sensor orientation are discussed.
Keywords: direct and integrated sensor orientation; GPS; inertial measurement; Physical Geography; Geology; Remote Sensing; Imaging Science & Photographic Technology